Human resources for health at the district level in Indonesia: the smoke and mirrors of decentralization - Harahap Nida P; Heywood Peter F (BMC, 2009)
Abstract Background In 2001 Indonesia embarked on a rapid decentralization of government finances and functions to district governments. One of the results is that government has less information about its most valuable resource, the people who provide the services. The objective of the work reported here is to determine the stock of human resources for health in 15 districts, their service status and primary place of work. It also assesses the effect of decentralization on management of human resources and the implications for the future. Methods We enumerated all health care providers (doctors, nurses and midwives), including information on their employment status and primary place of work, in each of 15 districts in Java. Data were collected by three teams, one for each province. Results Provider density (number of doctors, nurses and midwives/1000 population) was low by international standards - 11 out of 15 districts had provider densities less than 1.0. Approximately half of all three professional groups were permanent public servants. Contractual employment was also important for both nurses and midwives. The private sector as the primary source of employment is most important for doctors (37% overall) and increasingly so for midwives (10%). For those employed in the public sector, two-thirds of doctors and nurses work in health centres, while most midwives are located at village-level health facilities. Conclusion In the health system established after Independence, the facilities established were staffed through a period of obligatory service for all new graduates in medicine, nursing and midwifery. The last elements of that staffing system ended in 2007 and the government has not been able to replace it. The private sector is expanding and, despite the fact that it will be of increasing importance in the coming decades, government information about providers in private practice is decreasing. Despite the promise of decentralization to increase sectoral "decision space" at the district level, the central government now has control over essentially all public sector health staff at the district level, marking a return to the situation of 20 years ago. At the same time, Indonesia has changed dramatically. The challenge now is to envision a new health system that takes account of these changes. Envisioning the new system is a crucial first step for development of a human resources policy which, in turn, will require more information about health care providers, public and private, and increased capacity for human resource planning.